INTERVENÇÃO LÚDICO-SIMBÓLICA JUNTO A PORTADORES DE DISPEPSIA FUNCIONAL - Rímoli, Fábia (2010)
This study focuses on ludic-symbolic group intervention involving patients with functional dyspepsia (FD), a gastrointestinal disorder characterized by pain or discomfort on the upper abdomen area without identifiable cause by conventional diagnostic means. The present study aims to analyze the stress level of FD patients and connect it to the ludic-symbolic group intervention data. This is an exploratory-descriptive qualitative research.The group intervention uses active imagination techniques and the subjects stress level is evaluated with LIPP Adults Stress Symptoms Inventory (ISSL). The group consists of twelve members, mostly women; half of the participants are aged between 20 and 50 and the rest is older. Analysis of interview data shows that all group members have associated the beginning of their symptoms to emotional conflicts, focalizing scenes and situations as stressing factors that have triggered their FD. The symbolic analysis of the group interventions is based on Carl Gustav Jung s analytical psychology. Results show that the participants presented reduction of FD symptoms and of stress levels: initially, eight subjects were at the resistance stage, one at the alert stage and three of them presented no stress; by the end of the ludic-symbolic group intervention, three subjects were at the resistance stage, one remained at the alert stage and eight presented no stress. This transformation occurred after the symptoms regarded as symbols of emotions and feelings through symbolic play-action, and after having them integrated into consciousness by making psychic connections between mind and body to recognize actions taken or to be taken to avoid confrontations accelerate and crystallize symptoms of functional dyspepsia, from the standpoint of analytical psychology.